PENGARUH KINERJA KEUANGAN DAN MEKANISME CORPORATE GOVERNANCE (CG) TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) PERBANKAN SYARIAH (Studi Empiris pada Perbankan Syariah Indonesia periode 2011- - Hafsah Umri Salsabila (AKT 16 UMY 341, 2016)
This research aim to examine the influence of financial performance and the mechanism of Corporate Governance (CG) towards Islamic Social Reporting (ISR) disclosure in the Islamic Banking. Return On Asset (ROA), Capital Adequacy Ratio (CAR) and Non Performing Financing (NPF) as indicators financial performance variables. The size of sharia supervisory board, board size and the frequency of BOC meeting to be an indicator variable mechanism CG. This research subject are registered in Islamic banking Financial Services Authority. The data that used are secondary data from annual report of the bank published consecutively in 2011-2014. The research using purposive sampling method so we get 10 banks that meets the criteria of 12 banks in Indonesia. the tools used in this research is the analysis of multiple linear regressed. The results showed ROA, NPF, size of sharia supervisory board and the frequency of BOC meeting does not affect the disclosure of ISR Islamic banking. Variable board size positive and significant impact on the disclosure of ISR while the variable CAR significant negative effect on the disclosure of ISR. Keywords: Islamic Social Reporting (ISR). Return On Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), size of the Sharia Supervisory Board, the Board of Commissioners size and frequency of BOC meeting.